Physician Renewal of Chronically Prescribed Controlled Substances Based on Urine Drug Test Results - Fatima Hosain; Josephine Lee; Ashar Ata; Ravneet K. Bhullar; Andrew K. Chang (SAGE Publishing, 2019)
Objective: The effect of specific urine drug testing (UDT) results on physician prescribing habits has not been well described. The primary objective was to report renewal rates of chronically prescribed controlled substances based on types of inconsistent UDT results. Methods: We conducted a retrospective chart review over a 5-month period comparing prescription renewals rates for patients with consistent versus inconsistent UDTs. Inconsistent UDTs were defined by prescribed drug not detected or the presence of heroin, cocaine, nonprescribed opioids, nonprescribed benzodiazepines, or marijuana. Results: Of the 474 UDTs reviewed, 214 (45.1%) were inconsistent. The most common findings among inconsistent UDTs, including overlapping results, were prescribed drug not detected (26.8%) and the presence of marijuana (20.7%), nonprescribed opioids (9.9%), and nonprescribed benzodiazepines (6.1%). In contrast, cocaine (5.5%) and heroin (0.4%) were less likely to be found on UDTs for this population. The relative risk (RR) of prescription renewal was 0.64 (95% CI 0.57-0.71) for inconsistent UDTs versus consistent UDTs. Within the inconsistent UDTs, the renewal rates when marijuana (79.6%) or nonprescribed opioids or benzodiazepines (63.6%) were present were much higher than when heroin or cocaine were present (0.0%; P < .001). Patients whose prescribed controlled substance was not detected had a 55.8% renewal rate. Conclusions: Prescription renewal rates were high when patient UDTs contained nonprescribed marijuana, opioids, and benzodiazepines, or when the prescribed drug was not detected. Prescription renewal rates were low when illicit drugs, such as heroin and cocaine, were detected.